Bhabani Bhattacharya Vs ‘He Who Rides A Tiger’ - Singh, Ajay Kr. (Journal of Advanced Research in English & Education, 2021)
Bhabani Bhattacharya’s ‘He Who Rides a Tiger’ is yet another novel of man’s epic struggle against the unjust social equations which are as old as the ancient vedic civilization. It is the story of a blacksmith, Kalo, living in a small town, Jharana, in Bengal, and his daughter, Chandra Lekha. It is set against the backdrop of a widespread famine of Bengal of 1943. Though ‘He Who Rides a Tiger’ and ‘So Many Hungers’ treat the theme of hunger, exploitation and debasement of man, ‘He Who Rides a Tiger’ is no rehash of the latter novel. It launches a scathing critisism on the evil of caste system which has been the bane of Indian society. Arguably the writer’s best novel, it touches the pulse of the irony of Indian social life. The Indian social realities are presented with increasing bitterness within the perspective of the freedom movement. Its greatness as a piece of literature lies in its assertion of tremendous potentialities of the spiritual growth of man, and a thorough exposure of an imperfect social system. How to cite this article:  Singh AK. Bhabani Bhattacharya Vs ‘He Who Rides A Tiger’. J Adv Res Eng & Edu 2020; 5(1): 16-19. DOI: https://doi.org/10.24321/2456.4370.202003